دور دار الثقافة في تعزير الفعل الثقافي وحفظ التراث المحلي - بن حمو, بختة (كلية الأدب العربي والفنون, 2025)
تتناول هذه الدراسة موضوع "دور دار الثقافة في تعزيز الفعل الثقافي وحفظ التراث المحلي – ولاية الشلف أنموذجا، وهي دراسة تندرج ضمن تخصص إدارة الأعمال الفنية والثقافية، وتهدف إلى فهم وتحليل مدى مساهمة دار الثقافة في الحفاظ على الهوية الثقافية للمجتمع المحلي، من خلال أنشطتها ومبادراتها المختلفة. انطلقت الدراسة من إشكالية رئيسية مفادها:إلى أي مدى تسهم دار الثقافة في ولاية الشلف في حفظ التراث المحلي وتعزيزه؟ وتمت معالجتها من خلال منهجين: وصفي تحليلي لفهم الأطر النظرية للثقافة والتراث، وميداني اعتمادا على استبيانات ومقابلات موجهة لشرائح مختلفة من المجتمع المحلي ورواد دار الثقافة. تضمن الفصل الأول الإطار النظري للمفاهيم الأساسية المرتبطة بالثقافة والتراث، وأهداف دور الثقافة، بينما خُصص الفصل الثاني لدراسة تطبيقية تمثلت في تحليل فعاليات المهرجان الثقافي المحلي للفنون والثقافات الشعبية بدار الثقافة بالشلف، من حيث أهدافه، أنشطته، وتأثيره على الوعي الثقافي والمجتمعي. أظهرت النتائج أن دار الثقافة تلعب دورا محوريا في تنشيط الحياة الثقافية، ونقل التراث المحلي إلى الأجيال الجديدة من خلال المهرجانات، الورشات، الأمسيات، والعروض التفاعلية. كما تبين وجود تحديات تؤثر على أدائها، أبرزها ضعف الإمكانيات المادية، ونقص الوعي الثقافي لدى بعض الفئات، والحاجة إلى موارد بشرية مؤهلة. وفي ضوء هذه النتائج توصي الدراسة بضرورة تعزيز البنية التحتية الثقافية، وتكثيف البرامج الموجهة للأطفال والشباب، وتنظيم فعاليات في مختلف بلديات الولاية، إضافة إلى دعم الفنانين المحليين، وتوسيع الشراكات مع مؤسسات التعليم والمجتمع المدني من أجل تحقيق استمرارية وفعالية في حفظ التراث وتعزيز الفعل الثقافي. This study explores the role of the House of Culture in promoting cultural activity and preserving local heritage in the Wilaya of Chlef, as a model of cultural governance and community engagement. Falling under the field of Cultural and Artistic Management, the research seeks to understand how cultural institutions contribute to safeguarding collective identity and enhancing cultural awareness in society. The central research question investigates: To what extent does the House of Culture in Chlef contribute to preserving and promoting local heritage? The study adopts a descriptive and analytical approach to define theoretical concepts, alongside a field-based methodology involving surveys and interviews with youth, cultural actors, and frequent visitors to the institution. The first chapter offers a theoretical framework, discussing key concepts such as culture, tangible and intangible heritage, and the institutional role of cultural centers. The second chapter presents a case study of the Local Festival of Arts and Popular Cultures, organized by the House of Culture in Chlef, analyzing its objectives, activities, audience engagement, and cultural impact. Findings reveal that the House of Culture plays a vital role in activating the cultural scene, fostering creativity among young people, and transmitting local heritage through festivals, workshops, artistic exhibitions, and literary evenings. However, the institution faces challenges such as limited funding, low cultural awareness among certain groups, and insufficient qualified staff. Based on these findings, the study recommends strengthening cultural infrastructure, diversifying programs to reach different age groups, organizing decentralized events across the Wilaya, supporting local artists, and enhancing collaboration with educational institutions and civil society organizations. These measures aim to ensure the sustainability of cultural action and the effective preservation of local heritage.
ولاية شلف أنموذجا
Keywords: الثقافة،الفعل الثقافي،التراث الثقافي،دارالثقافة،المهرجان الثقافي